2023
DOI: 10.1111/nph.18976
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen isotope fractionation in carbohydrates of leaves and xylem tissues follows distinct phylogenetic patterns: a common garden experiment with 73 tree and shrub species

Abstract: Recent methodological advancements in determining the nonexchangeable hydrogen isotopic composition (δ 2 H ne ) of plant carbohydrates make it possible to disentangle the drivers of hydrogen isotope ( 2 H) fractionation processes in plants.Here, we investigated the influence of phylogeny on the δ 2 H ne of twig xylem cellulose and xylem water, as well as leaf sugars and leaf water, across 73 Northern Hemisphere tree and shrub species growing in a common garden.2 H fractionation in plant carbohydrates followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…The drought-induced variation in the 2 H-enrichment in OM among individual tree species might be partially explained by differences in growth strategies and physiological responses between angiosperm and gymnosperm species ( Schuler et al. 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The drought-induced variation in the 2 H-enrichment in OM among individual tree species might be partially explained by differences in growth strategies and physiological responses between angiosperm and gymnosperm species ( Schuler et al. 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…It should also be considered that we only worked with tobacco plants in this study. Yet, a recent study demonstrated that δ 2 H values of carbohydrates across a large set of tree and shrub species show distinct phylogenetic differences ( 40 ). Consequently, cellulose isotope models may include order-, family-, or genera-specific 2 H-fractionation factors if comparisons are made across different species.…”
Section: Discussionmentioning
confidence: 99%
“…In the chloroplast, NADPH can be produced during the photosynthetic photolysis reaction of water by the enzyme (ferredoxin-NADP + reductase, EC 1.18.1.2). The hydride transferred to NADPH is 2 H-depleted and considered responsible for the large 2 H-fractionation observed during autotrophic biosynthesis of plant organic matter ( 7 , 14 , 32 , 39 , 40 ). NADPH can also be produced by the tricarboxylic acid cycle (cytosolic NADP-dependent isocitrate dehydrogenase involved in ammonia assimilation, EC 1.1.1.42), the malate valve [responsible for redox homeostasis, oxalacetate as precursor of aspartate and other amino acids (AA)], and the oxidative pentose phosphate pathway [glucose-6-phosphate dehydrogenase (EC 1.1.1.49) and 6-phosphogluconate dehydrogenase (EC 1.1.1.44)].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation